Firms as producers vs. consumers of skills : an optimal inventory strategy - Burkart, Franziska [Verfasser]; Pfeifer, Harald [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2017)
"This paper addresses the circumstances under which firms are willing to make long-term investments in a skilled workforce and produce a high-quality workforce themselves rather than rely on skills that are produced elsewhere (within the education system or by other companies). The authors apply the inventory theory to strategic HR planning in order to explain how firms decide on their optimal 'inventory of skills' produced ahead of time to meet future demand. The authors use detailed information on different costs and benefits of training investments from the firm's perspective (BIBB CBS 2012) and apply a negative binomial model. The results show that firms are willing to invest in a larger inventory of skilled workers, i.e. to train more apprentices, firstly, if the costs of producing and retaining these skills (overage costs) are lower, secondly, if the costs of being short of skills in the future (underage costs) are higher, and thirdly, given an identical cost structure, if the demand for skills is likely to be high in the future. The findings have important policy implications for firms' incentives to invest in apprenticeship training." (Authors' abstract, BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; Betrieb; Ausbildungsverhalten; Bildungsinvestition; Bildungskosten; Qualifizierung; Personalauswahl